Effectiveness of holistic interventions for people with severe chronic obstructive pulmonary disease: systematic review of controlled clinical trials. - Ulugbek Nurmatov; Susan Buckingham; Marilyn Kendall; Scott A Murray; Patrick White; Aziz Sheikh; Hilary Pinnock (PLoS ONE)
Background Despite a well-recognised burden of disabling physical symptoms compounded by co-morbidities, psychological distress and social isolation, the needs of people with severe chronic obstructive pulmonary disease (COPD) are typically poorly addressed. Aim To assess the effectiveness of interventions designed to deliver holistic care for people with severe COPD. Methods We searched 11 biomedical databases, three trial repositories (January 1990-March 2012; no language restrictions) and contacted international experts to locate published, unpublished and in-progress randomised controlled trials (RCTs), quasi-RCTs and controlled clinical trials (CCTs) that investigated holistic interventions to support patients with severe COPD in any healthcare context. The primary outcome was health-related quality of life (HRQoL). Quality assessment and data extraction followed Cochrane Collaboration methodology. We used a piloted data extraction sheet and undertook narrative synthesis. Results From 2,866 potentially relevant papers, we identified three trials: two RCTs (from United States and Australia), and one CCT (from Thailand): total 216 patients. Risk of bias was assessed as moderate in two studies and high in the third. All the interventions were led by nurses acting in a co-ordinating role (e.g. facilitating community support in Thailand, providing case-management in the USA, or co-ordinating inpatient care in Australia). HRQoL improved significantly in the Thai CCT compared to the (very limited) usual care (p<0.001), in two sub-domains in the American trial, but showed no significant changes in the Australian trial. Exercise tolerance, dyspnoea, and satisfaction with care also improved in the Thai trial. Conclusions Some 15 years after reports first highlighted the unmet needs of people with severe COPD, we have been unable to find robust trial evidence about interventions that can address those needs. There is an urgent need to develop and evaluate holistic care interventions designed improve HRQoL for people with severe COPD. Systematic review registration PROSPERO (CRD42012002430).